Electromagnetic characteristics of in vivo nerve fibers at the terahertz-far-infrared band - Guo, Lianghao; Xu, Duo; Wang, Kaicheng; Sun, Yuankun; Zhang, Qin; Ning, Hui; Lu, Chang; Wang, Shaomeng; Gong, Yubin (Frontiers in Bioengineering and Biotechnology, 2022)
How terahertz signals perform in the neural system has attracted widespread interest in the life sciences community. Relevant experimental reveals that in animal nerve cells, the myelin sheath of the nerve axon has a higher refractive index than the intracellular and extracellular fluids in the Terahertz-far-infrared (THz-FIR) frequency band. This makes THz-FIR wave transmission possible in nerve fibers. Based on this premise, this article carries out the following work from the theoretical level to investigate the electromagnetic (EM) characteristics of in vivo nerve fibers at the THz-FIR band. First, the EM transmission model of the nerve fibers is established and studied theoretically. The dispersion curves of THz-FIR wave modals transmission in nerve fibers are calculated, which predict that nerve fibers can act as dielectric waveguides for transmitting THz-FIR waves and the THz-FIR waves can transmit at speeds up to 108 m/s. Second, a mode matching algorithm is proposed, which is named RNMMA, to calculate the transmission characteristics of THz-FIR waves at the nodes of Ranvier. The scattering matrix obtained from the proposed algorithm is in good agreement with the results from EM simulation software, which reveals how THz-FIR signals are transmitted forward through the nodes of Ranvier with low loss.